Adult gastroenterologists' views on transitional care: Results from a survey. Issue 8 (28th August 2019) - Kumagai, Hideki; Kudo, Takahiro; Uchida, Keiichi; Kunisaki, Reiko; Sugita, Akira; Ohtsuka, Yoshikazu; Arai, Katsuhiro; Kubota, Mitsuru; Tajiri, Hitoshi; Suzuki, Yasuo; Shimizu, Toshiaki
Abstract: Background: In 2018, Japanese guidelines for autonomy support of patients with inflammatory bowel disease (IBD) in the transitional period were published. These guidelines, however, were prepared mainly by pediatric gastroenterologists. In order to improve such supportive guidelines, it is necessary for pediatric gastroenterologists to be aware of the attitudes and expectations of adult gastroenterologists. Accordingly, the first Japanese national survey designed to explore the views of adult gastroenterologists regarding successful transitional care was conducted. Methods: The survey involved institutions at which adult gastroenterologists in the Ministry of Health, Labor and Welfare of Japan's Inflammatory Bowel Diseases Study Group, were working. Physicians were contacted by conventional mail, and their answers were not anonymized. A total of 100 eligible adult institutions were identified. Further specific subgroup analysis was conducted. Results: A response rate of 34% was achieved. Seventy‐six percent of the respondents had experienced some degree of difficulty when accepting patients with childhood‐onset IBD referred from pediatric gastroenterologists. With regard to the ideal form of medical care for adolescent patients with IBD, transfer to adult care was supported by 94% of the respondents. Only 27% of respondents, however, stated they would have no hesitation in accepting patients referred from pediatric care centers. Two crucial areas requiring improvement were identified: inadequate clinical summaries and lack of patient independence from their parents/caregivers. Conclusions: The present survey results reinforce the importance of a transitional program of education for childhood‐onset IBD patients and the need to improve communication between adult and pediatric gastroenterologists.